Continuous local bupivacaine wound infusion with neuraxial morphine reduces opioid consumption after cesarean delivery. (2nd December 2019) - Zaretsky, Michael; Wood, Cristina; Nivens, Traci; McLaughlin, Gerald; Zuk, Jeannie; Pan, Zhaoxing; Chow, Franklin
Abstract: Background: As a part of a quality improvement program, maternal postoperative opioid use and pain scores were compared between those receiving continuous infusion of bupivacaine for local incisional pain control with multimodal pain management and neuraxial morphine versus multimodal pain management with neuraxial morphine alone. Objective: We compared postoperative opioid use and pain scores between the multimodal pain management group with neuraxial morphine and the group receiving multimodal pain management, neuraxial morphine, and continuous infusion of bupivacaine for local incisional pain control. Study design: A retrospective cohort analysis of cesarean deliveries from January of 2015 through March of 2016 was undertaken. Deliveries were grouped by utilization of continuous infusion of bupivacaine for local incisional pain control. For each postoperative day, the average daily opioid use, antiemetic use and pain scores were determined. Patients received 1–2 tablets oxycodone–acetaminophen (5–325 mg) every 4 h as needed with oxycodone 5–10 mg immediate release tablets every 4 h as needed for breakthrough pain in addition to acetaminophen and ibuprofen. Total dose of narcotic, antiemetic use, and pain scores was compared between groups utilizing t -test for continuous variables and chi square for categorical data. A linear mixed model with unstructured covariance was utilized to analyze the daily dose of narcotic and pain scores from postoperative day 1 through day 4. Results: Patients in the standard multimodal group with neuraxial morphine used more opioids versus those receiving continuous wound infusion of bupivacaine in total postoperative dosing (122.79 ± 61.92 mg versus 89.88 ± 51.38 mg, p = .0063). There was a statistically significant difference between the standard group and local infusion of bupivacaine group on postoperative days 1 and 2 (32.79 ± 15.56 mg versus 22.13 ± 15.73 mg, p = .0011 and 40.25 ± 19.84 mg versus 29.13 ± 14.58 mg, p = .0018, respectively). There was no difference in narcotic use for postoperative days 3 and 4. There was a higher mean number of antiemetic doses in the standard group (0.31 ± 0.70 versus 0.10 ± 0.30, p = .0396). Pain scores did not differ between groups, although there was a correlation between opioid dosing and pain scores. The standard group received more IV ketorolac (87.72 ± 42.01 mg versus 64.50 ± 53.3 mg, p = .0165) and more IV acetaminophen (634.89 ± 706.42 mg versus 375.0 ± 490.29 mg, p = .0315) within the first 24 h postoperatively. In addition, the standard group received more oral acetaminophen (6969.67 ± 3230.14 mg versus 5248.75 ± 2711.71 mg, p = .0064). No difference was seen in regard to ibuprofen between groups. These results remained constant when adjusted for differences in gestational age, variation in intraoperative opioid dosing, as well as differences in uterine incision type. Conclusion: We found a significant reduction in postoperative opioid use when continuous infusion of bupivacaine for local incisional pain control was added to our standard pain management with neuraxial morphine after cesarean delivery. As a result of this quality improvement initiative, we have implemented this intervention universally as a part of our multimodal postoperative pain management strategy.